Stillbirths, Neonatal Morbidity, and Mortality in Health-Facility Deliveries in Urban Gambia - Camara, Bully; Oluwalana, Claire; Miyahara, Reiko; Lush, Alyson; Kampmann, Beate; Manneh, Kebba; Okomo, Uduak; D'Alessandro, Umberto; Roca, Anna (Frontiers in Pediatrics, 2021)
Background: The Gambia Demographic and Health Survey 2013 data showed that up to 63% of deliveries in the country occur in health facilities. Despite such a high rate, there are few facility-based studies on delivery outcomes in the country. This analysis ancillary to a randomised control trial describes occurrence of poor pregnancy outcomes in a cohort of women and their infants delivering in a government health facility in urban Gambia. Methods: Using clinical information obtained during the trial, we calculated rates of poor pregnancy outcomes including stillbirths, hospitalisation and neonatal deaths. Logistic regression was used to calculate odds ratio (OR) and 95% confidence interval (CI) in the risk factors analysis. Results: Between April 2013 and 2014, 829 mothers delivered 843 babies, including 13 stillbirths [15.4 (7.1-23.8)] per 1,000 births. Among 830 live born infants, 7.6% (n=63) required hospitalisation during the 8-week follow-up period. Most of these hospitalisations (74.6%) occurred during the early neonatal period (<7 days of life). Severe clinical infections (i.e. sepsis, meningitis and pneumonia) (n=27) were the most common diagnoses, followed by birth asphyxia (n=13), major congenital malformations (n=10), jaundice (n=6) and low birth weight (n=5). There were sixteen neonatal deaths, most of which also occurred during the early neonatal period. Overall, neonatal mortality rate (NMR) and perinatal mortality rate (PMR) were 19.3 (CI: 9.9-28.7) per 1,000 live births and 26.1 (CI: 15.3-36.9) per 1,000 total births, respectively. Severe clinical infections and birth asphyxia accounted for 37% and 31% of neonatal deaths, respectively. The risk of hospitalisation was higher among neonates with severe congenital malformations, low birth weight, twin deliveries, and those born by caesarean section. Risk of mortality was higher among neonates with severe congenital malformations and twin deliveries. Conclusion: Neonatal hospitalisation and deaths in our cohort were high. Although vertical interventions may reduce specific causes of morbidity and mortality, data indicate the need for a holistic approach to significantly improve the rates of poor pregnancy outcomes. Critically, a focus on decreasing the high rate of stillbirths is warranted.